Development of Islamic Cultural History Learning Media Based on Google Sites for Junior High School Students - Khairina, Khairina; Mardianto, Mardianto (research, training and philanthropy institution Natural Aceh, 2025)
This study aims to develop and present Islamic Cultural History learning media based on Google Sites that can be used in class VII of Madrasah Tsanawiyah Negeri 2 Deli Serdang. This study uses a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model developed by Dick and Carey. This study involves several stages of needs: needs analysis, media design, product development, media implementation, and evaluation of results. The data collection instruments include media expert validation sheet questionnaires, Islamic Cultural History teacher response questionnaires, and student response questionnaires. The validation results show that the developed media obtained a score of 95,38% from the media expert validator (very feasible category) and 100,00% from the material expert validator (very feasible category). The teacher's response to the media obtained a score of 88,00% (very feasible category), while the student's response obtained a score of 93,79% (very feasible category). Based on the evaluation results, it can be concluded that the Islamic Cultural History learning media based on Google Sites that has been developed meets the eligibility criteria and is ready to be used in the learning process in class VII of State Islamic Junior High School 2 Deli Serdang.